Research on lifelong learning culture - Kamarudin, Diyana; Omar, Safiynaz; Azit, Azizan
The purpose of this research is to assess the impacts of lifelong learning skills and job performance among MBA program students. Four lifelong learning skills were included in this study, which are: managerial skill, self-esteem, interpersonal skills, hard skills, and soft skills. Since there are high rate of unemployment among graduates nowadays, it is important to know the feedback from university students on how the courses that they took provide them with the skills for employability in the future. This study employed 101 MBA program students from Universiti Malaysia Pahang (UMP), Gambang Pahang as a sample. Feedbacks from students were gathered through a set of questionnaires, and the data were analysed through SPSS 23.0. The result shows that self-esteem and interpersonal skills had the most significant effect towards job performance, among the other factors. Meanwhile, managerial skills had the weakest effect towards job performance.